2016
DOI: 10.1186/s13071-016-1635-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in malaria burden and transmission in sentinel sites after the roll-out of long-lasting insecticidal nets in Papua New Guinea

Abstract: BackgroundPapua New Guinea exhibits a complex malaria epidemiology due to diversity in malaria parasites, mosquito vectors, human hosts, and their natural environment. Heterogeneities in transmission and burden of malaria at various scales are likely to affect the success of malaria control interventions, and vice-versa. This manuscript assesses changes in malaria prevalence, incidence and transmission in sentinel sites following the first national distribution of long-lasting insecticidal nets (LLINs).Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 33 publications
(41 reference statements)
5
81
1
Order By: Relevance
“…12 Genetic diversity was high for both P. vivax and P. falciparum throughout PNG. Diversity of the P. vivax markers PvMS16 and Pvmsp1F3 was similar to diversity reported from other endemic settings 42,75,77,78 and similar to previous reports from the north coast of PNG. 42,44,79 Despite high variability in complexity of infection, P. falciparum genetic diversity based on the Pfmsp2 marker was also similar among different geographic areas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…12 Genetic diversity was high for both P. vivax and P. falciparum throughout PNG. Diversity of the P. vivax markers PvMS16 and Pvmsp1F3 was similar to diversity reported from other endemic settings 42,75,77,78 and similar to previous reports from the north coast of PNG. 42,44,79 Despite high variability in complexity of infection, P. falciparum genetic diversity based on the Pfmsp2 marker was also similar among different geographic areas.…”
Section: Discussionsupporting
confidence: 90%
“…51,76 A study from Indonesia showed a positive correlation between the rate of polyclonal infections and annual parasite incidence indicating that polyclonality might provide a complementary gauge of local transmission intensity. 33 In the case of P. falciparum in PNG, this measure correlates well with prevalence, however in this and other studies, 77,78 P. vivax infections had a high proportion of multiple clones even in areas with decreasing transmission, so polyclonality may be less effective for determining the transmission of the latter species.…”
Section: Discussioncontrasting
confidence: 41%
“…The methods used in this household survey have already been described [19]. Briefly, a finger prick blood sample was taken from consenting individuals aged >5 months old from 30–35 randomly selected households in each village.…”
Section: Methodsmentioning
confidence: 99%
“…Historically, the Southwest Pacific region, in particular PNG and Solomon Islands, has endured some of the highest P. vivax transmission anywhere in the world (Gething et al 2012;Gething et al 2011;Organisation 2013). This region has a natural, gradual decline in malaria endemicity from west to east with high transmission in PNG, moderate-to-high in Solomon Islands and low transmission in Vanuatu (Gething et al 2012) that has been accentuated by recent control efforts (Hetzel et al 2016;Koepfli et al 2015a;. Our previously published population genetic data from PNG and Solomon Islands , combined with new samples from ongoing studies within Solomon Islands and Vanuatu, presents a unique opportunity to understand the population genetics of P. vivax in context with declining transmission.…”
Section: Introductionmentioning
confidence: 99%